Biodegradation of phorbol esters in Jatropha curcas (linn.) kernel by fungi for production of poultry feed - Najjar, Azhar (2014)
Poultry industry in Malaysia is highly dependent on imported feeds like corn and soybean meal. The cost of poultry production then depends on the price of feeds according to the global market. With the increase in feed ingredients, the cost of production would be accordingly affected. Hence, it is pertinent to find local alternative feed that can partially replace corn or soybean meal, to reduce the dependency on imported feeds. Jatropha curcas has gained importance as a source of seed oil for the production of biodiesel. The seed kernel also shows potential as a feed ingredient for poultry due to its high protein and low fiber content. However, the presence of phorbol esters as the main toxic compound makes the kernel unsafe as animal feed. Hence, the main objective of this study was to treat Jatropha seed kernel by fungal fermentation to produce a safe feed ingredient for poultry. The specific objectives of this study were to determine the levels of phorbol esters in the local Jatropha seed kernel, to treat the dried ground kernel by submerged fermentation, to conduct enzymes and cells bioassays and,to evaluate the fermented kernel as tested was that the selected non toxic and non pathogenic fungal strains could degrade the phorbol ester present in Jatropha kernel to a safe level for the production of poultry feed. Two fungal isolates obtained from garden soil and five endophytes from Achillea fragrantissima plant in Saudi Arabia were used for degrading the phorbol esters. These fungi were identified as T. harzianum (isolates TUT1 and TUT2), P. sinensis (isolate TUP8), C. cladosporioides (isolate TUC9) and F. chlamydosporum (isolates TUF1, TUF10 and TUF11) based on their morphological characteristics and internal transcribed spacer regions (ITS) sequence analysis. All 7 fungal strains were non-toxic to both normal Chang liver cells and mouse cell lines. The optimum fungal growth was in potato dextrose broth (PDB) medium at temperature 28°C and pH 5.5. Phorbol esters in the phorbol esters-rich fraction prepared from the seed kernel were analyzed by LC-DAD-ESIMS. Four phorbol ester derivatives were detected, where Peak 1 was identified to be 12-deoxy-16-hydroxyphorbol. Peaks 2, 3 and 4 were phorbol esters that possess the same diterpene moiety, namely, 12-deoxy-16-hydroxyphorbol. Quantitative analysis of phorbol esters by high performance liquid chromatography showed a value of 2.78 mg phorbol-12-myristate 13-acetate (PMA) equivalent per g dry weight of Jatropha kernel. The phorbol ester-rich fraction prepared contained 66.72 mg PMA equivalent per g dry weight. The addition of different levels of phorbol ester-rich fraction (1-3 g) to 30 ml PDB did not inhibit the growth of the 7 fungal strains after 14 days incubation. All fungal strains were able to utilize phorbol esters-rich fraction as a carbon source in PDB as well as in mineral salt broth (MSB) media. The fungal dry weight increased significantly (p<0.05) in the presence of 2 g of phorbol ester-rich fraction after 30 days incubation. The values obtained for T. harzianum JQ350879.1 and control (without phorbol ester-rich fraction) were 3227.3 and 440.0 mg, respectively. The phorbol esters present in phorbol esters-rich fraction or in methanolic extract or kernel were degraded in the range of 67.7 to 99.7% after 30 days of incubation by the fungal strains. The maximum removal of phorbol esters was by T. harzianum JQ350879.1 for all the three different substrates. The level of phorbol esters was reduced by 99.7% by T. harzianum JQ350879.1. Lipase activity was significantly higher (p<0.05) for all strains grown on olive oil medium containing phorbol esters. However, only three isolates i.e., P. sinensis JQ350881.1, C. cladosporioides JQ517491.1 and F. chlamydosporum JQ517492.1 showed both lipase and esterase activities. The presence of phorbol esters also induced esterase activity significantly (p<0.05). In the cytotoxicity bioassay with Chang liver and NIH 3T3 cell lines, cell viabilities were significantly (p<0.05) increased (84.3-96.5%) when compared to the control (0.3-0.4%) by fungal treatment of phorbol estersrich fraction. In the feeding trial experiment, 20% of Jatropha kernel treated with T.harzianum JQ350879.1 was included in broilers diet (treated group) to replace 50% of soybean meal. Birds in the control group were fed a diet containing 40% soybean meal. The body weight gain and feed consumption of broilers in treatment group were 1996.0g and 5049.5 g/bird, respectively, and that for control were 2181.8 g and 5596.8 g/bird,respectively. The feed conversion ratio (feed intake over weight gain) was similar between broilers in treated and control groups (2.52 vs. 2.56). Blood parameters results were comparable with normal values, showing no signs of toxicity. Mortality rate of birds in the treated group (7/60) was not significantly different from the control group (8/60). There was no histopathological evidence of abnormal change to liver and kidney tissues of broilers in treatment group. In conclusion, Jatropha seed kernel was found to contain four derivatives of phorbol esters at high concentrations, which make the plant a toxic variety. The levels of phorbol esters were successfully alleviated to a safe level by submerged fermentation with non toxic Trichoderma spp. and fungal endophytes. Fungal treated Jatropha kernel could be used as a feed ingredient to partially replace soybean in poultry diet without apparent toxicity symptoms.